THE STRATEGIC DECISION OF COMMERCIAL SPONSORSHIP AMONG INDONESIA ADVERTISERS: A DELPHI STUDY - La Ode Muhammad Restu Prada; Rizal Edi Halim (Jurnal Ekonomi dan Bisnis, 2019)
The study attempts to discern how Indonesia advertiser look at the strategic decision ofcommercial sponsorship within today Indonesia market, which was done by using Delphimethod. The relative importance of commercial sponsorship is examined within the context ofoverall today marketing and overall advertising approach, budget allocation, and the expertsconfident regarding the future growth of Indonesia commercial sponsorship. The discussiongoes more specific to understand what marketing objective that will be better achieved throughcommercial sponsorship approach. The result shows that within the context of marketingobjective, commercial sponsorship still regarded as a high important approach. However, dueto its cost inefficiency nature, Indonesia advertisers reach to the consensus that commercialsponsorship approach should be focused on to deliver marketing objective that aim to deliverproduct experience to the consumers.Keywords: Delphi method, Sponsor, Commercial Sponsorship, Sponsorship Property,Advertiser, Marketing Objective